2012
DOI: 10.1111/j.1365-2699.2012.02786.x
|View full text |Cite
|
Sign up to set email alerts
|

Divergent evolution in the polymorphic granular poison‐dart frog, Oophaga granulifera: genetics, coloration, advertisement calls and morphology

Abstract: Aim To investigate the intra-specific genetic divergence and phenotypic diversification in Oophaga granulifera, analysing phylogeographical patterns, population structure, coloration and traits potentially involved in reproductive isolation.Location Costa Rica.Methods Our phylogeographical analysis used the mitochondrial genes cytochrome b and 16S. We sequenced the two markers in 28 individuals belonging to 10 populations and 16 individuals from nine populations, respectively. The population structure was anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 85 publications
0
28
0
Order By: Relevance
“…The dorsal coloration of O. granulifera ranges from red to green hues (Wang ; Brusa et al. ). We found that not only the hue but also the brightness and saturation of color vary with latitude.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The dorsal coloration of O. granulifera ranges from red to green hues (Wang ; Brusa et al. ). We found that not only the hue but also the brightness and saturation of color vary with latitude.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a number of intermediate populations with intermediate coloration have been discovered between the green and red localities (Brusa et al. ). We selected four populations of O. granulifera (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likely data sources to further validate this method include: a study by Gosden, Stoks & Svensson () investigating female blue‐tail damselflies ( Ischnura elegans ) colour morphs in Europe; Ozgo's () study of shell polymorphism in grove snails ( Cepaea nemoralis ) in continental Europe; Brusa et al . 's () study of the granular poison dart frog ( Oophaga granulifera ) colour morphs in Costa Rica; and Arista et al . 's () study of colour morphs of the scarlet pimpernel flower ( Lysimachia arvensis ) in the western Mediterranean and southern Europe.…”
Section: Discussionmentioning
confidence: 99%
“…1). Although there is some evidence that geographical barriers might play an important role in the diversification of some Central American lineages (Hagemann & Pr€ ohl, 2007;Rudh et al, 2007;Wang & Shaffer, 2008), the geographical proximity and overlapping distribution of some of the Oophaga species suggest that factors other than strict geographical isolation may also influence diversification (Maan & Cummings, 2009;Crothers et al, 2011;Brusa et al, 2013;Cummings & Crothers, 2013).…”
Section: Introductionmentioning
confidence: 99%